Perioperative Matrix Metalloproteinase-2 and Matrix Metalloproteinase-9 Profiles in Acute and Chronic Subdural Hematomas - Bartłomiej Kulesza; Mateusz Krakowiak; Dorota Luchowska-Kocot; Jacek Kurzepa; Cezary Grochowski; Ryszard Maciejewski (Journal of Clinical Medicine, 2026)
Background: Acute subdural hematoma (ASDH) and chronic subdural hematoma (ChSDH) differ substantially in their pathophysiology, clinical course, and outcomes. Matrix metalloproteinases (MMPs), particularly MMP-2 and MMP-9, have been implicated in blood–brain barrier disruption, extracellular matrix remodeling, and inflammatory processes involved in both traumatic brain injury and ChSDH. However, direct comparisons of perioperative MMP profiles between ASDH and ChSDH and their relationships with clinical characteristics remain limited. The aim of this study was to compare perioperative MMP-2 and MMP-9 concentrations in patients with ASDH and ChSDH and explore their associations with selected clinically relevant parameters. Methods: Thirty patients undergoing surgical treatment for subdural hematoma were prospectively enrolled, including 10 patients with ASDH and 20 with ChSDH. Serum samples were collected before surgery and on postoperative day 3, and hematoma content was obtained intraoperatively. MMP-2 and MMP-9 concentrations were measured using enzyme-linked immunosorbent assay. Results: Patients with ASDH had significantly higher MMP-9 concentrations in hematoma content (p = 0.002) and postoperative serum (p = 0.029) than patients with ChSDH, whereas MMP-2 concentrations did not differ significantly between the groups. In the ChSDH group, both MMP-2 and MMP-9 concentrations were significantly lower in hematoma content than in preoperative and postoperative serum, while no significant perioperative changes were observed in patients with ASDH. Higher MMP-2 concentrations in hematoma content were associated with lower leukocyte counts and smaller midline shift, whereas higher hematoma MMP-9 concentrations were associated with lower APTT and CRP concentrations after FDR correction. These findings suggest distinct perioperative MMP-2 and MMP-9 profiles in acute and chronic subdural hematomas. Conclusions: This study provides a direct comparison of perioperative MMP-2 and MMP-9 profiles in serum and hematoma content between patients with ASDH and ChSDH while also exploring their associations with selected clinically relevant parameters.